Lower Frequency of CD62Lhigh and Higher Frequency of TNFR2+ Tregs Are Associated with Inflammatory Conditions in Type 1 Diabetic Patients - Monika Ryba; Karolina Rybarczyk-Kapturska; Katarzyna Zorena; Małgorzata Myśliwiec; Jolanta Myśliwska (Mediators of Inflammation)
Diabetes type 1 is a chronic autoimmune disease in which insulin-producing cells are gradually destroyed by autoreactive T cells. Human regulatory cells play important role in controlling autoimmunity, and their qualitative or quantitative dysfunctions may result in ineffective suppression of autoreactive T cells. CD62L is a surface molecule that plays role in homing capabilities of Tregs, and only cells with high expression of CD62L have high suppressive potential. Tregs are also characterized by the constant expression of TNFR2. The frequency of Tregs carrying TNFR2 is higher in inflammatory conditions. We investigated blood regulatory T cells with CD62L expression and regulatory T cells expressing TNFR2 in type 1 diabetic patients. We found differences in these populations when comparing to healthy individuals. We propose that these may be associated with inflammatory conditions that are present in patients with type 1 diabetes. The lower percentage of Tregs and Treg CD62Lhigh may contribute to ineffective suppression of proinflammatory cytokines production during type 1 diabetes.